Electric field control of the energy gap in ZnO and BaSnO3 films grown on PMN-PT - Bridoux, German (2024)
ZnO and BaSnO3 (BSO) thin films grown on Pb(Mg1/3Nb2/3)O3-PbTiO3 (PMN-PT) substrates have been studied using electrical resistance and photoconductivity (PC) spectra measurements under different applied electric fields on the substrate. The behavior of the resistance and the energy gap (EG) extracted from the PC spectra are modified by the polarization state of the substrate in the case of the ZnO film, while for BSO, these physical parameters depend on the strain imposed by the substrate when a voltage is applied on the PMN-PT. In the latter case, an in-plane tensile (compressive) strain leads to a reduction (increase) in the resistance and the energy gap when an external electric field is applied on the substrate. The behavior of ZnO and BSO can be explained by the different crystalline structure in both films and by the fact that ZnO is also a piezoelectric material. In ZnO, a change in the polarization state of the substrate is associated with an imposed strain and an induced polarization on the film that leads to a modification of the band bending and hence of the energy gap. In the case of BSO, a shift of the impurity and conduction band generates a modification of the energy gap for the different types of strain.